Deciphering the history of forest disturbance and its effects on landforms and soils – lessons from a pit-and-mound locality at Rogowa Kopa, Sudetes, SW Poland - Pawlik, Łukasz; Musielok, Łukasz; Migoń, Piotr; Wrońska-Wałach, Dominika; Duszyński, Filip; Kasprzak, Marek (Bulletin of Geography. Physical Geography Series, 2017)
The historical dimension of pit-and-mound topography has been studied at Mt Rogowa Kopa locality, Stołowe Mountains, SW Poland. This site represents one of the best developed regional examples of hummocky forest floor relief due to widespread tree uprooting and subsequent degradation of root plates. Through map analysis and dendrochronology the disturbance history was traced at least to the 1930s and most likely a strong wind episode from 1933 was the reason of forest calamity that resulted in nearly complete destruction of the original stand. However, the forest affected was a planted Norway spruce monoculture, introduced and managed at least till the beginning of 20th century, not a natural forest. The windthrow niche was then used by beech whose individuals preferentially chose mounds to grow, conserving hummocky microtopography. Changes in soil evolutionary pathways brought about by wind-driven disturbance include both homogenization (rejuvenation) and horizonation (differentiation). Evidence of soil rejuvenation includes decrease of organic carbon content and pH increase in the upper parts of soils developed on mounds in comparison with undisturbed references soils. Soil texture was relatively homogenized in pits and mounds. Dating of pit-and-mound microrelief by means of soil properties (organic carbon content, iron forms) was only partly successful. Although young age of pits and mounds is evident, the actual age inferred from soil properties was underestimated by a few tens of years. Evaluation of factors potentially controlling the propensity to widespread treethrow suggests that the type of forest is a far more important variable than local abiotic factors of bedrock geology, regolith characteristics, and slope inclination.